Conformance Testing and Analysis of Synchrophasor Communication Message Structures and Formats for Wide Area Measurement Systems in Smart Grids - Adeyemi Charles Adewole; Raynitchka Tzoneva (Institute of Advanced Engineering and Science, 2017)
The renewed quest for situational awareness in power systems has brought about the use of digital signal processing of power system measurements, and the transmission of such data to control centres via communication networks. At the control centres, power system stability algorithms are executed to provide monitoring, protection, and control in order to prevent blackouts. This can be achieved by upgrading the existing Supervisory Control and Data Acquisition (SCADA) systems through the deployment of newly proposed power system synchrophasor-based applications for Wide Area Monitoring, Protection, and Control (WAMPAC). However, this can only be done when there is a complete understanding of the methods and technologies associated with the communication network, message structure, and formats required. This paper presents an analysis of the IEEE C37.118 synchrophasor message framework, message formats, and data communication of synchrophasor measurements from Phasor Measurement Units (PMUs) for WAMPAC schemes in smart grids. A newly designed lab-scale testbed is implemented and used in the practical experimentation relating to this paper. Synchrophasor measurements from the PMUs are captured using a network protocol analyzer software-Wireshark, and the compliance of the synchrophasor message structures and formats captured was compared to the specifications defined in the IEEE C37.118 synchrophasor standard.